2020
DOI: 10.3389/fonc.2020.605361
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Cationic Amphiphilic Drugs and Derivatives to Engage Lysosomal Cell Death in Cancer Treatment

Abstract: A major confounding issue in the successful treatment of cancer is the existence of tumor cell populations that resist therapeutic agents and regimens. While tremendous effort has gone into understanding the biochemical mechanisms underlying resistance to each traditional and targeted therapeutic, a broader approach to the problem may emerge from the recognition that existing anti-cancer agents elicit their cytotoxic effects almost exclusively through apoptosis. Considering the myriad mechanisms cancer cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Recently, it was shown that small molecules can trigger pyroptosis in breast tumour cells 78 . In addition, cationic amphiphilic drugs could be repurposed to induce lysosomal cell death in cancer 20 . Pyroptosis and lysosomal cell death overlap or culminate with non-regulated necrotic cell death and therefore couldn't be absolutely excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that small molecules can trigger pyroptosis in breast tumour cells 78 . In addition, cationic amphiphilic drugs could be repurposed to induce lysosomal cell death in cancer 20 . Pyroptosis and lysosomal cell death overlap or culminate with non-regulated necrotic cell death and therefore couldn't be absolutely excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer membrane targeting is currently developing as an effective therapeutic strategy [10][11][12] . Antimicrobial drugs with ionophoric properties as salinomycin [13][14][15] , monensin 16,17 , azurin 4 and gramicidin 18,19 , as well as amphiphilic drugs with potential to locally perturb composition of lipid bilayers throughout the cell 11,20 , have been repurposed to target membranes in cancer. One of the most promising approaches involves drugs with heterogeneous anticancer activity that simultaneously hit multiple membrane-related targets within the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Lysosome-dependent cell death (LDCD), characterized by lysosomal destabilization and requiring LMP, is now distinguished as a subclass of programmed cell death (153). Though lysosomal rupture has been observed as an ultimate consequence of canonical cell death processes (154), primary LMP activates a death program in LDCD and can be differentiated by novel assay systems (155,156). LMP does not generate defining morphological alterations (157) and is therefore classified at the molecular level by release of lysosomal luminal contents including proteolytic cathepsin enzymes to the cytosol, where cathepsins function in a variety of contexts as cell death executioners (158).…”
Section: Lysosomes In Cell Deathmentioning
confidence: 99%
“…We have reported that 5-(N,N-hexamethylene) amiloride (HMA), a derivative of the FDA-approved potassium-sparing diuretic amiloride and a member of the broader class of cationic amphiphilic drugs (CADs) [ 14 , 15 , 16 ], is cytotoxic toward cultured breast cancer cells independent of caspase activity [ 17 ]. HMA reduces the viability of breast cancer cells of differing molecular profiles with equal efficiency [ 17 ], which is significant as breast cancer subtypes (luminal or basal, estrogen/progesterone receptor-positive (ER/PR+), HER2−amplified (HER2+), or receptor-negative (ER/PR/HER2−)) are variably resistant to chemotherapeutics and targeted drugs [ 18 ].…”
Section: Introductionmentioning
confidence: 99%